Determination of Service Centers Along the East Coast Corridor of Ogan Komering Ilir Regency - Rozak Indra Praja; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
This study aims to determine service centers along the East Coast Corridor of Ogan Komering Ilir Regency using two analytical approaches: facility service index analysis and rank-size rule analysis. Perroux's growth center theory (1950) is applied to understand how districts with higher facilities and populations can stimulate surrounding economic growth. The facility service index analysis identifies the availability and distribution of public facilities in each district, while the rank-size rule maps population distribution to pinpoint potential service centers. The results show that Air Sugihan District holds potential as the primary service center due to its facilities, while Tulung Selapan District is designated as a settlement center given its largest population. With a balanced development strategy, it is expected that this can create equitable service access, foster economic growth, and strengthen the socioeconomic resilience of communities in Ogan Komering Ilir Regency.